Effect of Different Solutions on Two Milled Esthetic Restorative Materials - Yousief, Salah A.; Alzahrani, Khames T.; ALSharif, Maha F.; Alamri, Asalah H.; Harthi, Basmah A.; Ashgan, Mai T.; Almalki, Samah S.; Tumbukani, Ranin A.; Bugshan, Safanah A.; Boqshan, Fisal A.; Aljarafi, Shahad A.; Ibrahim, Bayan A.; et al. (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Today, ceramic plays a vital role in restorative dentistry. Common uses include full-coverage crown, inlays, onlays, and ceramic bridges. The demands for esthetics in dental restoration continue, new technologies tend to improve the material properties and develop new methods for application. Objective: This study aimed to evaluate the effect of different solutions on two milled esthetic restorative materials. Material and methods: In this study, a total of thirty blocks samples were machine milled by the aid of computer-aided design & computer-aided manufacturing (CAD/CAM) system. The samples were divided according to the material of construction into two main groups. Each group was composed of 15 samples as follows: Group I: constructed from milled composite resin blocks. Group II: constructed from milled feldspathic porcelain blocks. All sample groups were then immersed in 20ml of artificial saliva for 24 hours to be a baseline assessment. Results: Spectrophotometer measurements of all the groups and subgroups revealed statically significant higher mean ΔE values for ceramic groups than the composite resin groups. All changes in the colour were clinically acceptable except for ceramic samples immersed in acid media. Conclusion: By reducing the pH value, increasing the acidity of the immersion media that led to an increase in the surface roughness of the tested restorative materials (composite resin and ceramic).